New approach for modeling the contribution of NSM FRP strips for shear strengthening of RC beams - Bianco, V. (2010)
This paper presents the main features of an analytical model recently developed to predict the near-surface mounted (NSM) fiber-reinforced polymer (FRP) strips shear strength contribution to a reinforced concrete (RC) beam throughout the beam's loading process. It assumes that the possible failure modes that can affect the ultimate behavior of an NSM FRP strip comprise: loss of bond (debonding); concrete semiconical tensile fracture; mixed shallow-semicone-plus-debonding; and strip tensile fracture. That model was developed by fulfilling equilibrium, kinematic compatibility, and constitutive law of both the adhered materials and the bond between them. The debonding process of an NSM FRP strip to concrete was interpreted and closed-form equations were derived after proposing a new local bond stress-slip relationship. The model proposed also addressed complex phenomena such as the interaction between the force transferred to the surrounding concrete through bond stresses and concrete fracture as well as the interaction among adjacent strips. The main features of the proposed modeling strategy are shown along with the main underlying physical-mechanical concepts and assumptions. Using recent experimental data, the predictive performance of the model is assessed. The model is also applied to single out the influence of relevant parameters on the NSM technique effectiveness for the shear strengthening of RC beams.